Role of Reactive Oxygen Species in the Progression of Type 2 Diabetes and Atherosclerosis - Hideaki Kaneto; Naoto Katakami; Munehide Matsuhisa; Taka-aki Matsuoka (Mediators of Inflammation)
Type 2 diabetes is the most prevalent and serious metabolic disease all over the world, and its hallmarks are pancreatic 𝛽-cell dysfunction and insulin resistance. Under diabetic conditions, chronic hyperglycemia and subsequent augmentation of reactive oxygen species (ROS) deteriorate 𝛽-cell function and increase insulin resistance which leads to the aggravation of type 2 diabetes. In addition, chronic hyperglycemia and ROS are also involved in the development of atherosclerosis which is often observed under diabetic conditions. Taken together, it is likely that ROS play an important role in the development of type 2 diabetes and atherosclerosis.